PROGRAM KEMITRAAN MASYARAKAT KELOMPOK IBU BAYI BERAT BADAN LAHIR RENDAH DI RSUD SANJIWANI GIANYAR - Made Ayu Cynthia Windasari; Anak Agung Oka Lely; Ni Komang Rani Juli Antari; Made Dwi Mahendra (JURNAL SEWAKA BHAKTI, 2021)
Low Birth Weight (LBW) babies have 20-fold higher risk to develop complications of disease and mortality. This condition causes babies to be treated in the Neonatal Intensive Care Unit (NICU) for a long time. Sanjiwani Hospital is a referral center for East Bali Region which has NICU facilities and provide health services for LBW babies. Growth and development disorders often experienced by these babies. The interviews result with mothers who have LBW babies in Sanjiwani haspital, there are problems that they do not have good ability to care LBW babies, to providing nutrition and stimulation for support normal growth & development and also do not have stimulation tools. Based on these problems, we provide counseling, interactive dialogue, training to increase their knowledge and skills, and also supporting developmental stimulation tools to them. After counseling, there are an increase knowledge of LBW infant care, breastfeeding techniques, catch-up nutrition and infant development for about 82%. The improvement of partner skills in performing the kangaroo method, baby massage and developmental stimulation are also increase for about 88%. This increase is quite significant and reach the expected target